Analisis faktor yang mempengaruhi minat mahasiswa menjadi young entrepreneur pasca pandemi Covid-19 - Endah Nurmahmudah; Titin Suhartini; Rissa Nuryuniarti (Jurnal Kajian Manajemen dan Wirausaha, 2021)
The COVID-19 pandemic that has hit the world, including Indonesia, has destroyed the order of life in all fields, especially the economic sector. Various corporations have experienced a decline in income due to decreased purchasing power, as a result of which there have been layoffs everywhere and many companies have collapsed. This incident automatically increases the unemployment rate sharply. After the COVID-19 pandemic or so-called new normal, economic activity has not returned to normal, but this can be an opportunity as well as a challenge for those who are sensitive and dare to take risks to become entrepreneurs. Students as educated young people are prepared to be able to face real world challenges with the provision of knowledge, freedom and a supportive environment and lucrative income expectations. This study aims to determine the faktors that influence student interest in becoming young entrepreneurs after the COVID-19 pandemic. The method used is multiple linear regression and the sample is students of the University of Muhammadiyah Tasikmalaya semester 5 who have received entrepreneurship courses. The results of the study can be concluded that the faktors of freedom, environment, entrepreneurship education together influence the motivation of students to become young entrepreneurs. Meanwhile, the income expectation faktor has no positive effect on student motivation to become young entrepreneurs after the COVID-19 pandemic t test result < t table (1.442 < 1.960).